Relationship Between Green Product Design, Reverse Logistics Product Disposition and Business Performance Among Electrical and Electronic Manufacturing Firms - Khor, Kuan Siew (2013)
This thesis is derived from the concept of reverse supply chain management and focuses on environmental and economic perspectives of reverse logistics product disposition. The current business environment accentuates the need for recoverable products, and manufacturers are encouraged to design products that facilitate multiple recovery capabilities. Returns with higher residual value deserve attention because business benefits from reverse logistics potentially improve firms‟ performance by extending the useful life of products which had underperformed earlier than expected. The product‟s structure and composition challenge reverse logistics implementation and these necessitate quantitative research on anteceding factors, particularly green product design and resource commitment, on reverse logistics product disposition. The study also examined the successive influence of reverse logistics product disposition on business performance and investigated whether institutional pressures moderate capability-performance relationships. A mail survey was administered to 177 ISO14001 certified E&E manufacturers in Malaysia and 89 usable responses were empirically tested. The research findings revealed that green product design (design for disassembly and design for environment) and resource commitment were antecedents of reverse logistics product disposition. Consequently, repair, remanufacture and recycling contributed to business performance (profitability and sales growth). By maintaining environmental compliance and shareholder interest, hierarchical regression analyses revealed that institutional pressures exerted significant moderating influence to warrant desirable outcome from reverse logistics activities, that is, repair, recondition, remanufacture, recycle and disposal. If firms have interest on reverse logistics implementation, disassemblability takes precedent over recyclability of products. When risk of penalties from regulatory violation is present, firms are motivated to generate benefits via extended producer responsibility. This study provided insights into antecedents and outcome of reverse logistics and acknowledged the moderating influence of institutional pressure, particularly, coercive and ownership pressure. Instead of analysing green product design and reverse logistics as components of green supply chain management, the relationship between both components was investigated. Limitations and suggestions for future research are discussed.